The path to enlightenment : Svayambhu Stora [i.e., stotra] - Samantabhadra, Acharya Svami; Goyal, Devendra Kumar (New Delhi : Radiant Pub., 2000)
Sanskrit text with English translation in Jaina Stotras and prayers.
Under the auspices of Jain Mission
Keywords: Jainism -- Prayers and devotion